Особенности развития партийной системы Украины: от плюрализма к ограниченной конкуренции - Molochko, Pavlo (ELIPSA Publishing House, 2014)
World researchers tend to touch upon the question of the limited influence of political parties more and more often. The author surveys the level of fragmentation of the party system of Ukraine on the basis of the empirical approach, as well as counts the index of democracy of Ukraine from 1998 to 2012. The results indicate that after a long period of stability, the decline in the influence of political parties on the democratic processes in Ukraine has recently become apparent. On the basis of these results, the author analyses the reasons for limiting the role of parties in the political processes of Ukraine.
PECULIARITIES OF THE DEVELOPMENT OF THE PARTY SYSTEM OF UKRAINE: FROM PLURALISM TO THE LIMITED COMPETITION
Keywords: Political science; Political parties; Party sysytem; Index of democracy; Party system of Ukraine; Партійна система України; Індекс демократизації